Design of dual‐mode high efficiency tri‐band power amplifier using input and output harmonic control technology. Issue 10 (16th July 2021) - Shen, Ce; He, Songbai; Peng, Jun; Yao, Tingting; You, Fei
Abstract: In this article, a design method for a tri‐band power amplifier (PA) with dynamic drain bias voltage is presented. Continuous operation modes are used to expand the impedance design space. In the input and output matching networks, harmonic control circuits are set up to improve efficiency. The load harmonic impedances are obtained by continuous theory. Bias network and harmonic short circuit are used in the input matching network to control harmonics and obtain stop‐band. Dynamic drain bias enables the PA to adapt to different emission environments. With input and output harmonic control technology, a 0.9, 1.5, and 2.1 GHz GaN PA is designed to achieve high efficiency in different modes. The measured efficiencies of the fabricated PA at all three bands are more than 58.6%. At 1.5 GHz, when driven with a 20 MHz LTE signal with a 7 dB peak‐to‐average power ratio, by applying digital pre‐distortion, the PA prototype maintains an adjacent channel power ratio of better than −48.7 dBc.